Pengaruh Substitusi Pati Jagung, Pati Kentang, dan Tapioka terhadap Kekerasan dan Sifat Berminyak Pilus - Nur Wulandari; Rosita Hardwianti Imam; Ulfah Syarifah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2016)
The production process of pilus at the industrial level still faces problems related to brittle texture and oily taste. The objective of this study was to determine the effect of substitution of corn starch, potato starch, and tapioca on the quality of pilus snack, particularly to overcome brittle texture and oily taste problems. The research stage were characterization of raw materials, preparation of pilus with substitution treatments, and characterization of pilus produced. The starch used had moisture content of 11.86-21.04% (db), pH 4.22-5.13, starch content 92.42-95.13% (db), and amylose to amylopectin ratio 0.40-0.51. The distribution of particle size of starch varied greatly, with a breakdown viscosity value of 2114-8628 cP and viscosity setback of 735-2097 cP. Results showed that several characteristics of pilus snack were affected by substitution treatments, including higher bulk density (0.40-0.52 g/mL), harder texture (4.11-4.74 kgf), lower fat content (27.07-29.76%), and higher hardness rating score (3.0-3.6). The best substitution treatment was demonstrated by 5% corn starch, which reduced brittle texture (hardness increased to 4.74 kgf) and also reduced oily taste (oil content decreased to 27.07%). Pearson’s correlation test between physicochemical parameters of substituted starch with hardness (R2=0.539) and strongly correlated with oily properties (R2=0.733) of pilus.